Rapid and One-Pot Synthesis of Aryl Ynamides from Aryl Alkynyl Acids by Metal-Free C-N Cleavage of Tertiary Amines - Yong Liu; Xiaoyong Liu; Hongwei Li; Shengmei Guo (Molecules)
Herein a rapid, metal-free, and highly efficient synthesis of aryl ynamides from aryl alkynyl acids has been described. This approach, utilizing tertiary amines as an amino source via metal-free C-N cleavage, enabled the construction of a diverse range of aryl ynamides with medium to excellent yields (33 examples, up to 95% yield). This reaction exhibits significantly enhanced efficiency compared to the conventional stepwise approach involving aryl alkynyl acids and secondary amines. It can be successfully scaled up, providing a practical and environmentally benign strategy for alkynamide synthesis.